PROSPECTS FOR DEVELOPMENT OF THE VENTURE CAPITAL AND PRIVATE EQUITY MARKET - Zasępa, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
By 1990, venture capital (VC) and private equity (PE) were little known class of assets in which engaged a few institutional investors. With the development of this market and the emergence of high rates of return interest in forming a class showed larger financial institutions and individual investors. As a result, too many investors involved too many resources, which resulted in the fact that VC funds engaged in the company in a position that does not qualify them to investment . Performance of venture capital funds started to decline and impair the quality of the portfolio. The portfolio companies were not able to translate the received funds for dynamic development. That is why many investors withdrew from involvement in established asset class, and the number of active funds began to fall. There is then an evolution in the approach to venture capital investment to more capital efficient investment and new business models. Venture capital industry is based on continuous innovation revolution and therefore it is possible to observe the change of funds business model in the future. The aim of the paper is to characterize the changing trends in the venture capital funds and an indication of the possible direction of future changes in the asset class and the confirmation of the hypothesis that the levels of investment activity funds will be reduced and sought to levels observed in 1996–1998 and 2002–2005.